Liability and Large-Scale, Long-Term Hazards - Ringleb, Al H.; Wiggins, Steven N. (Journal of Political Economy, 1990)
This paper analyzes the application of liability to large-scale, long-term hazards. The key features distinguishing such hazards are the long temporal separation between exposure to a hazard and disease and the large damages when injuries finally emerge. The large scale of damages creates a strong incentive to avoid liability payments, and the long temporal separation creates numerous avenues through which parties can avoid paying possible damage awards. The analysis focuses on the incentive to avoid paying damages by vertically divesting production tasks associated with serious occupational risks. Such divestiture can lower liability costs if the small firm operating the risky stage goes out of business before latent injuries emerge or has insufficient assets to pay damages and declares bankruptcy when suits are filed. The paper then presents an empirical regression analysis of small-firm entry into the U.S. economy between 1967 and 1980, the period in which liability laws were changing. The point estimate is that, ceteris paribus, liability changes appear to have led to a large increase in small corporations in hazardous sectors. Hence the empirical analysis shows widespread attempts to avoid liability by shielding assets through divestiture.